2009
DOI: 10.1007/s10103-009-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid etching duration on tensile bond strength of composite resin bonded to erbium:yttrium–aluminium–garnet laser-prepared dentine. Preliminary study

Abstract: The purpose of this study was to compare the tensile bond strength of composite resin bonded to erbium:yttrium-aluminium-garnet (Er:YAG) laser-prepared dentine after different durations of acid etching. The occlusal third of 68 human third molars was removed in order to expose the dentine surface. The teeth were randomly divided into five groups: group B (control group), prepared with bur and total etch system with 15 s acid etching [37% orthophosphoric acid (H(3)PO(4))]; group L15, laser photo-ablated dentine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
7
0
5
Order By: Relevance
“…Although literature has used settings of 10 Hz [7,10,25,28] for dentin pretreatment, the current study and former ones [8,26,36] demonstrated that the use of lower frequency, as low as 2 Hz, provides effective ablation rates to the target tissues. These lower frequencies allow suitable ablation and decrease the heat generated from this energy transference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although literature has used settings of 10 Hz [7,10,25,28] for dentin pretreatment, the current study and former ones [8,26,36] demonstrated that the use of lower frequency, as low as 2 Hz, provides effective ablation rates to the target tissues. These lower frequencies allow suitable ablation and decrease the heat generated from this energy transference.…”
Section: Discussionmentioning
confidence: 99%
“…This absorbed residual energy is transformed into heat that will accumulate into dentin. The main concern when laser heating occurs is the occurrence of thermal damage to the underlying dentin collagen matrix [23] which may cause collagen denaturation in deep regions of dentin [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Chousterman et al reported signifi cant increase in tensile bond strength of the samples when the etching time was prolonged up to 90 s [ 44 ].…”
Section: Fig 730mentioning
confidence: 99%
“…Ito et al 17 found that a short etching duration (10s) provided higher bond strength than extended etching (30s, 60s) of samples contaminated with saliva and blood. Chousterman et al 18 recommended that extension of acid etching time to 90s will improve tensile bond strength of composite bonded to Er:YAG laser-prepared dentin. On the other hand, according to Oliveira et al 19 etching time had no significant effect on the bond strength of the adhesives to dentin.…”
Section: Introductionmentioning
confidence: 99%